2009
DOI: 10.1159/000200077
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Leydig Cell Origin and Development

Abstract: Male sexual differentiation is a complex process requiring the hormone-producing function of somatic cells in the gonad, including Sertoli cells and fetal Leydig cells (FLCs). FLCs are essential for virilization of the male embryo, but despite their crucial function, relatively little is known about their origins or development. Adult Leydig cells (ALCs), which arise at puberty, have been studied extensively and much of what has been learned about this cell population has been extrapolated to FLCs. This approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 236 publications
(121 reference statements)
5
93
0
2
Order By: Relevance
“…In our gonadal samples, the immunohistochemical expression pattern of SF-1 in adult Leydig cells was different from the expression pattern in fetal Leydig cells, which possibly reflects a functional difference. It has been suggested that fetal Leydig cells represent a different population than adult Leydig cells (27,28). SF-1-mediated induction of steroidogenic enzymes has not been studied in detail in these two different populations, and it is conceivable that in vivo steroidogenesis by adult Leydig cells is less dependent on SF-1 compared with steroidogenesis by fetal Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our gonadal samples, the immunohistochemical expression pattern of SF-1 in adult Leydig cells was different from the expression pattern in fetal Leydig cells, which possibly reflects a functional difference. It has been suggested that fetal Leydig cells represent a different population than adult Leydig cells (27,28). SF-1-mediated induction of steroidogenic enzymes has not been studied in detail in these two different populations, and it is conceivable that in vivo steroidogenesis by adult Leydig cells is less dependent on SF-1 compared with steroidogenesis by fetal Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…At 12.5 dpc in the mouse (7-8 GW in the human), as the cords are forming, the fetal Leydig cells start to differentiate from mesenchymal-like stem cells within the interstitial spaces between the cords (Byskov 1986, Huhtaniemi & Pelliniemi 1992, O'Shaughnessy et al 2006, Ostrer et al 2007. Differentiation of the fetal Leydig cells is regulated by desert hedgehog (DHH), secreted by the Sertoli cells (Pierucci-Alves et al 2001), while platelet-derived growth factor a (PDGFA) and the Arx homeobox gene are also involved (Griswold & Behringer 2009). Around 13.0 dpc, the peritubular myoid cells (PMC or PTM) start to develop (Pierucci-Alves et al 2001), although their origin remains uncertain (Cool et al 2008).…”
Section: Fetal Testis Developmentmentioning
confidence: 99%
“…The fetal Leydig cell population is the predominant source of circulating androgen in the fetus and is replaced after birth by the 'adult' population of cells which gives rise to the pubertal surge in testosterone (O'Shaughnessy et al 2006). These two Leydig cell populations appear to be distinct both functionally and morphologically, and while they arise separately, a connection between the precursor stem cells is possible but unknown (O'Shaughnessy et al 2006, Griswold & Behringer 2009). It has also been suggested, on the basis of a post-natal rise in androgens, that there is a third 'neonatal' population of Leydig cells in a number of species, including humans (Prince 2001).…”
Section: Leydig Cellsmentioning
confidence: 99%
“…Además, inducen la diferenciación de la población de células intersticiales y actúan manteniendo los gonocitos y las espermatogonias tempranas. La proliferación de las células sustentaculares ocurre solamente durante la vida fetal y prepuberal (Griswold & Behringer, 2009). Su actividad es controlada por la hormona folículoestimulante (FSH), la cual indirectamente influye en la producción de andrógenos por las células intersticiales (Nascimento et al, 2016).…”
Section: Desarrollo De Las Células Sustentaculares (De Sertoli)unclassified
“…Las células intersticiales se desarrollan en el compartimiento intersticial a partir de las células mesenquimales provenientes del epitelio celómico y mesonefros, aunque ciertos estudios plantean que tendrían un origen a partir de células de la cresta neural debido a similitudes que poseen con las células de la médula adrenal (O'Shaughnessy et al, 2006;Huber, 2006;Griswold & Behringer). Su función es la producción de andrógenos claves en la masculinización fetal y también son capaces de inducir el descenso testicular hacia el escroto (Klonisch et al, 2004;O'Shaughnessy et al, 2006).…”
Section: Desarrollo De Las Células Intersticialesunclassified